Safety and efficacy of Tet-regulated IL-12 expression in cancer-specific T cells - Alsaieedi, Ahdab (Oncoimmunology, 2018)
We explored whether engineering of T cell specificity and effector function improves immunotherapy of solid tumors. Although IL-12 can enhance cancer immunity, a strategy of safe IL-12 delivery without toxicity is currently lacking. We engineered T cells to express IL-12 controlled by the NFAT promoter responsive to TCR stimulation, or by the Tet-On promoter responsive to doxycycline. In vivo, NFAT-engineered T cells caused lethal toxicity, while Tet-engineered T cells were safe in the absence of doxycycline. Combining gene transfer of the melanoma-specific TRP2-TCR with Tet-IL-12 engineering revealed that temporal induction of IL-12 was essential to inhibit the growth of B16F10 melanoma tumors. Induced IL-12 increased the number of tumor-infiltrating T cells and also prevented the down-modulation of the TRP2-TCR and the associated up-regulation of the PD1 marker that was observed in the absence of IL-12. In addition, temporal induction of IL-12 expression also increased the number of plasmacytoid DC in the tumor micro-environment. We show that repeated induction of IL-12 can be used to enhance control of tumor growth without encountering systemic toxicity. The observation that TCR engineering combined with Tet-regulated IL-12 expression can achieve tumor immunity without the side effects that are usually associated with the in vivo use of IL-12 warrants translation of this concept into the clinic.